Application of computational fluid dynamics (CFD) for nanofluids - Kamyar, A.; Saidur, Rahman; Hasanuzzaman, M. (Elsevier, 2012)
Evaluating the heat transfer enhancement due to the use of nanofluids has recently become the center of interest for many researchers. This newly introduced category of cooling fluids containing ultrafine nano-particles (1-100 nm) has displayed fascinating behavior during experiments including increased thermal conductivity and augmented heat transfer coefficient compared to a pure fluid. This article reviews and summarizes the numerical studies performed in this area including conventional numerical methods as well as the new Lattice Boltzmann Method (LBM). Most of these computational simulations are in acceptable concordance with the results from experiments. However, there are some challenges to encounter when dealing with nanofluids. Changes might be necessary to mathematical models before simulation such as using two-phase models instead of single-phase models for nanofluids.